The Influence of a Single Preoperative Ketorolac Dose on Postoperative Opiate Consumption for Ambulatory Knee Arthroscopy: A Double Blinded Placebo Controlled Study. Issue 7 (21st July 2017) - Slone, Harris; Epperson, Thomas; Furse, Cory; Wolf, Bethany; Wilson, Sylvia
Objectives: Ketorolac is a non-steroidal anti-inflammatory known to decrease postoperative opiate requirements. While many studies have examined serial ketorolac doses over 48 hours, the optimal ketorolac dose for analgesia following ambulatory surgery is not established. We examined postoperative opiate consumption in morphine equivalents (ME) for patients receiving a randomized ketorolac dose for knee arthroscopy. Methods: Patients undergoing elective, outpatient knee arthroscopy were randomized a dose of ketorolac (0 mg, 7.5 mg, 15 mg, 30 mg) in a double blinded placebo controlled fashion. Postoperative opiate consumption was the primary outcome. Secondary endpoints were patient satisfaction score, Visual Analog Pain Scores (VAS) pre- and postoperative, side effects and total PACU time. Logistic regression was used to compare the results among the different ketorolac groups. Results: A total of 112 patients were enrolled with comparable patient and procedural characteristics in each group. Mean postoperative opiate consumption in ME was 6.36 mg across all groups. The median VAS at PACU arrival was 3.0 and at discharge was 1.6. Median patient satisfaction across all treatment groups was 9.8 out of 10. In univariate models, increased postoperative morphine consumption was associated with decreased ketorolac dose ( P =0.037) and female gender ( P =0.021). In a multivariable model, patients that received 7.5 fewer mg of ketorolac consumed on average 0.6 mg more ME postoperatively controlling for other factors ( P =0.034). Females consumed an average of 2.3 mg more opiates relative to males after controlling for ketorolac dose ( P =0.006). Ketorolac dose was not associated with the occurrence of side effects ( P =0.722). Side effects were associated with female gender ( P =0.023) and increased BMI ( P =0.022). Consumption of each additional 1 mg of postoperative ME had a 13% increase in the odds of having at least one side effect controlling for other factors ( P =0.026, 95% CI: 1.02-1.26). Conclusion: Decreased ketorolac dose is associated with increased opiate consumption controlling other factors. Increased opiate consumption may result in increased side effects, although this did not impact patient satisfaction.